2006
DOI: 10.1016/j.tsf.2006.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra and structural analysis in ZrOxNy thin films

Abstract: Raman spectroscopy has been used as a local probe to characterize the structural evolution of magnetron-sputtered decorative zirconium oxynitride ZrO x N y films which result from an increase of reactive gas flow in the deposition The lines shapes, the frequency position and widths of the Raman bands show a systematic change as a function of the reactive gas flow (a mixture of both oxygen and nitrogen). The as-deposited zirconium nitride film presents a Raman spectrum with the typical broadened bands, due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
8
22
0
2
Order By: Relevance
“…These Raman spectra can be compared to those obtained by Moura et al, who systemically investigated the ZrN and ZrO x N y compounds having FCC structures. [24] They are very similar to the Raman spectrum corresponding to the FCC ZrN phase containing a little oxygen. [24] Also, according to their results, the shifts of the peak positions towards the high frequency region that we observed in our spectra can correspond to structural defects.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These Raman spectra can be compared to those obtained by Moura et al, who systemically investigated the ZrN and ZrO x N y compounds having FCC structures. [24] They are very similar to the Raman spectrum corresponding to the FCC ZrN phase containing a little oxygen. [24] Also, according to their results, the shifts of the peak positions towards the high frequency region that we observed in our spectra can correspond to structural defects.…”
Section: Resultssupporting
confidence: 68%
“…[24] They are very similar to the Raman spectrum corresponding to the FCC ZrN phase containing a little oxygen. [24] Also, according to their results, the shifts of the peak positions towards the high frequency region that we observed in our spectra can correspond to structural defects. [24] According to our Raman analysis, it can be suggested that the contamination of nitrogen plays an important role in the stabilization of the FCC phase during milling.…”
Section: Resultssupporting
confidence: 68%
“…On the other hand, ZrN forbidden bands (the first order Raman scattering) are observed due to the disorder and imperfection of the structure caused by oxygen and carbon atoms in the lattice [30]. Constable [31] reported the presence of two bands; one due to the acoustic transition (173,241 cm -1 ) and the other to optic modes (473-580 cm -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…O compósito formado pela deposição de filmes finos de ZrN, ou pela formação de ZrN na superfície da zircônia por nitretação tem muitas aplicações [25,26], como revestimento protetor de ferramentas de corte e em moldes, como barreira a difusão, como contatos elétricos e, não menos importante, como revestimento decorativo [31,32]. ZrN tem cor dourada [15,33,34], mas é a possibilidade de controlar a cor do revestimento, mediante a deposição controlada de oxinitreto de zircônio que tem especial interesse para revestimentos decorativos, pois a razão O/N no filme determina a sua cor [26,33]. Revestimentos protetores e decorativos baseados em filmes finos de ZrN tem sido depositados sobre diferentes substratos, inclusive cerâmicos, por diferentes métodos de deposição.…”
Section: Introductionunclassified
“…Revestimentos protetores e decorativos baseados em filmes finos de ZrN tem sido depositados sobre diferentes substratos, inclusive cerâmicos, por diferentes métodos de deposição. Entre esses métodos, mencionamos aqui a deposição por pulverização catódica magnetron reativa dc e rf (reactive magnetron sputtering), a partir de alvo de Zr, e não-reativa, a partir de alvo de ZrN [13,21,34,35] e a deposição por evaporação térmica com feixe de elétrons em plasma reativo (ion plating) [33,34].…”
Section: Introductionunclassified